Smoke-free spaces: a decade of progress, a need for more? - Semple, Sean; Dobson, Ruaraidh; O'Donnell, Rachel; Zainal Abidin, Emilia; Tigova, Olena; Okello, Gabriel; Fernández, Esteve (BMJ, 2022)
Adoption of smoke-free measures has been one of the central elements of tobacco control activity over the past 30 years. The past decade has seen an increasing number of countries and proportion of the global population covered by smoke-free policies to some extent. Despite reductions in global smoking prevalence, population growth means that the number of non-smokers exposed to the harms caused by secondhand smoke remains high. Smoke-free policy measures have been shown to be useful in protecting non-smokers from secondhand smoke, and can additionally increase cessation and reduce smoking initiation. Policies tend to be aimed primarily at enclosed public or workplace settings with very few countries attempting to control exposure in private or semiprivate spaces such as homes and cars, and, as a result, children may be benefiting less from smoke-free measures than adults. Compliance with legislation also varies by country and there is a need for education and empowerment together with guidance and changing social norms to help deliver the full benefits that smoke-free spaces can bring. Restrictions and policies on use of electronic cigarettes (e-cigarettes) in smoke-free settings require more research to determine the benefits and implications of bystanders’ exposure to secondhand e-cigarette aerosol, dual use and smoking cessation.